Upconversion luminescence enhancement and lifetime based thermometry of Na(Gd/Lu)F4 solid solutions. (12th February 2019) - Yao, Lu; Li, Yongjin; Xu, Dekang; Lin, Hao; Peng, Yan; Yang, Shenghong; Zhang, Yueli
Abstract : Upconversion luminescence and lifetime based thermal sensing performance enhancements of NaGdF4 are achieved by a simple solid solution strategy. Abstract : Upconversion nanoparticles, whose thermal sensitivity performances are widely investigated, have attracted great attention recently. Enhancements of their upconversion luminescence and thermal sensing performances are of great importance. In the present paper, upconversion luminescence and lifetime based thermal sensing performance enhancements of NaGdF4 are achieved by a simple solid solution strategy and synthesis environment tuning. With Lu 3+ ion doping, Na(Gd/Lu)F4 :Yb, Er upconversion nanoparticles of hexagonal phase transformed into those of cubic phase. DFT calculations have been performed, and are in good agreement with experimental results. Higher temperature and lower NaOH contents in the precursor are adopted to prevent the phase transformation from the hexagonal phase to cubic phase. Na(Gd/Lu)F4 solid solutions of a pure hexagonal phase with enhanced luminescence performance are obtained. Both the FIR and lifetime based thermal sensing behavior of the β-Na(Gd/Lu)F4 solid solutions in the temperature range from 250 to 330 K are investigated. Compared with previous reports, β-Na(Gd/Lu)F4 solid solutions exhibit excellent sensitivity properties in terms of lifetime based thermometric properties. This work provides insight into the fabrication of efficient optical temperature probes, which may have a wide range of potential applications in the thermal sensing field.